Detection and clinical analysis of drug-induced antibodies related to β-lactam antibiotics - ZHENG Yangyang; WANG Rongpeng; ZHAO Jie; ZHUO Bingzheng; CHEN Feng (Zhongguo shuxue zazhi)
[Objective] To investigate the positive rate of drug-induced antibodies produced by the clinical application of β-lactam antibiotics, and analyze the differences in the detection methods and related influencing factors. [Methods] A total of 350 adult inpatients who developed anemia after using β-lactam antibiotics for 3 days or more in Inner Mongolia People's hospital were selected as the experimental group, and 240 adult inpatients treated with β-lactam antibiotics for 3 days or more who did not develop anemia as the control group. The drug-induced antibody tests, direct antiglobulin tests, and unexpected antibody screening were performed on both groups, and the influencing factors of drug-induced antibodies were analyzed. [Results] The numbers of positive cases of drug-induced antibody detected by the drug-coated red blood cell method in the experimental group and the control group were 12(12/350, 3.43%) and 2(2/240, 0.83%) respectively, with statistically significant differences (P<0.05). No drug-induced antibodies were detected in either group using the drug addition method. In the experimental group, the red blood cell method detected β-lactam drug-induced antibodies in 12 cases (12/350, 3.43%), while the drug added method detected 0 cases (0/350, 0.00%), with statistically significant differences (P<0.05). In the control group, the detection rates of two methods showed no statistically significant difference (P>0.05). In the experimental group, 7 cases of β-lactam antibodies were detected in the cephalosporin group (7/293, 2.40%) and 5 cases in the non-cephalosporin group (5/58, 8.62%), with statistically significant differences (P<0.05). There was no statistically significant difference between the second-generation and third-generation cephalosporin drugs (P>0.05). When the experimental group was stratified according to the history of blood transfusion and the blood type of patients, no statistically significant differences were observed between subgroups (P>0.05). [Conclusion] Anemia may be related to the production of drug-induced antibodies followingβ-lactam antibiotics treatment. Therefore, improving the clinical awareness of drug-induced antibodies to β-lactam antibiotics is of great significance to clarify the causes of anemia and reduce unnecessary blood transfusions.